Stable triple-wavelength random fiber laser based on fiber Bragg gratings - Awang Lah, Airull Azizi; Sulaiman, Abdul Hadi; Abdullah, Fairuz; Ambran, Sumiaty; Ng, Eng Khoon; Alresheedi, Mohammed Thamer; Mahdi, Mohd Adzir; Md Yusoff, Nelidya (MDPI, 2023)
We demonstrate a generation of three lasing wavelengths with the assistance of Rayleigh backscattering as the stabilizer of peak power variations. The proposed laser consists of a combination of the semiconductor optical amplifier (SOA) and erbium-doped fiber amplifier (EDFA) as the amplifying media. Three fiber Bragg gratings are employed as the selective wavelength selectors at 1544, 1547 and 1550 nm. At 110 mA SOA current and 18 dBm EDFA output power, a flattened output spectrum with 0.9 dB peak power variation is attained. In terms of stability, the maximum peak power fluctuation for the individual laser is 0.24 dB within 120 minutes observation period. Without the Rayleigh backscattering effect, the peak power flatness is severely degraded. This shows that the weakly distributed photons can be utilized as peak power stabilizers in fiber laser systems.